Perioperative immune checkpoint inhibition for colorectal cancer: recent advances and future directions - Chen, Jiao-Ting; Zhou, Yu-Wen; Han, Ting-Rui; Wei, Jun-Lun; Qiu, Meng (Frontiers in Immunology, 2023)
For colorectal cancer (CRC), surgical resection remains essential for achieving good prognoses (1, 2). Unfortunately, numerous patients with locally advanced CRC and metastatic CRC failed to meet surgical indications or achieve pathological complete response after surgery(2, 3). Perioperative therapy has been proven to effectively lower tumor staging and reduce recurrence and metastasis. Immune checkpoint inhibitors (ICIs) have shown unprecedented prolongation of survival time and satisfactory safety in patients with high microsatellite instability/deficient mismatch repair (MSI-H/dMMR), while the therapeutic effect obtained by patients with mismatch repair-proficient or microsatellite stable (pMMR/MSS) was considered minimal. However, recent studies found that certain CRC patients with dMMR/MSI-H presented intrinsic or acquired immune resistance, and pMMR/MSS CRC patients can also achieve better efficacy. Therefore, more predictors are required for screening patients with potential clinical benefits. Since the discovery of synergistic effects between immunotherapy, chemotherapy, and radiotherapy, different immunotherapy-based therapies have been applied to the perioperative therapy of CRC in an increasing number of research. This review comprehensively summarized the past and current progress of different combinations of immunotherapy in perioperative clinical trials for CRC, focusing on the efficacy and safety, and points out the direction for future development.